Mechanical characterization and numerical simulation of a subcutaneous implantable 3D printed cell encapsulation system. (June 2018) - Adamo, Federica; Farina, Marco; Thekkedath, Usha R.; Grattoni, Alessandro; Sesana, Raffaella
Abstract: Cell transplantation in bioengineered scaffolds and encapsulation systems has shown great promise in regenerative medicine. Depending on the site of implantation, type of cells and their expected function, these systems are designed to provide cells with a physiological-like environment while providing mechanical support and promoting long-term viability and function of the graft. A minimally invasive 3D printed system termed neovascularized implantable cell homing and encapsulation (NICHE) was developed in polylactic acid for subcutaneous transplantation of endocrine cells, including pancreatic islets. The suitability of the NICHE for long term in vivo deployment is investigated by assessing mechanical behavior of both fresh devices under simulated subcutaneous conditions and NICHE retrieved from subcutaneous implantation in pigs. Both experimental and numerical studies were performed with a focus on validating the constitutive material model used in the numerical analysis for accuracy and reliability. Notably, homogeneous isotropic constitutive material model calibrated by means of uniaxial testing well suited experimental results. The results highlight the long term durability for in vivo applications and the potential applicability of the model to predict the mechanical behavior of similar devices in various physiological settings.